OPTIMALISASI ZAT GIZI PADA PROSES PERKECAMBAHAN PEMBUATAN TAOGE : KAJIAN SUHU DAN LAMA PERENDAMAN - Wachid, Mochammad (Jurnal Gamma, 2006)
Bean sprouts has high nutrition value, cheap, and easy to get. The making process of bean sprouts is very simple, that is by germination process. Germination process increases digestion power because germination is a catabolic process that serves important nutrition for plant growth by hydrolytic reaction of reserve nutrition in the seed. Germination is affected by the condition and place. The aim of this study is to know the effect of submergence water and the duration of submergence to the bean sprouts' quality and the increase of the nutrition of bean sprouts. The result of this research shows that the temperature of water and the duration of submergence gives different quality and different increase of the nutrition of bean sprouts (water degree, dust degree, rendemen, vitamin c, fat degree, reduction sugar degree, protein degree, and density). From the result of this research, it is expected to the increasing of food quality. So, it will be implicated to better health quality of the people.